2020
DOI: 10.1111/and.13646
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contaminants and male infertility: Effects and mechanisms

Abstract: The global incidence of infertility has risen to 15% in contrast to 7%-8% in the early 1960s (Mascarenhas, Flaxman, Boerma, Vanderpoel, & Stevens, 2012). Over the past several decades, a significant deterioration in male reproductive health has been reported in association with increased industrialisation, which has contributed to a massive release of synthetic pollutants into the environment (Rim, 2017; Skakkebaek et al., 2016). The concerns over declining male reproductive health were elicited by one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 131 publications
(159 reference statements)
0
40
0
Order By: Relevance
“…Testosterone plays a key role in the initiation and maintenance of spermatogenesis, differentiation of male genital organs, and the production of secondary sexual characteristics. Any factor affecting the viability of Leydig cells and/or interfering with testicular steroidogenesis may cause endocrine regulation of spermatogenesis to be disrupted and impair fertility (Selvaraju et al, 2020).…”
Section: Figure 3 Mean Effect Of Different Antioxidants On Albino Rats' Sperm Morphologymentioning
confidence: 99%
“…Testosterone plays a key role in the initiation and maintenance of spermatogenesis, differentiation of male genital organs, and the production of secondary sexual characteristics. Any factor affecting the viability of Leydig cells and/or interfering with testicular steroidogenesis may cause endocrine regulation of spermatogenesis to be disrupted and impair fertility (Selvaraju et al, 2020).…”
Section: Figure 3 Mean Effect Of Different Antioxidants On Albino Rats' Sperm Morphologymentioning
confidence: 99%
“…After exposure to environmental contaminants, the epididymal epithelium is degenerates and the blood–epididymal barrier cannot control intraluminal microenvironment. Change in the micro‐architecture of the epididymis, accompanied by an increase in reactive oxygen species, impairs sperm maturation (Selvaraju et al., 2020). Maamar et al.…”
Section: Epigenetic Factors Affecting Sperm Maturationmentioning
confidence: 99%
“…Semen quality is the major predictor of male fertility outcome [6]. It was observed that environmental pollution unfavorably affects semen quality by impairing the process of spermatogenesis, steroidogenesis, Sertoli cell, and sperm functions, thereby leading to decreased male fertility [7,8]. Furthermore, there are numerous natural and man-made chemicals that are released into the environment daily and have deleterious impacts on human fertility.…”
Section: Introductionmentioning
confidence: 99%